Effects of chitosan on plant growth under stress conditions: similarities with plant growth promoting bacteria - Rojas-Pirela, Maura; Carillo, Petronia; Lárez-Velásquez, Cristóbal; Romanazzi, Gianfranco (Frontiers in Plant Science, 2024)
The agricultural use of synthetic pesticides, fertilizers, and growth regulators may represent a serious public health and environmental problem worldwide. All this has prompted the exploration of alternative chemical compounds, leading to exploring the potential of chitosan and PGPB in agricultural systems as a potential biotechnological solution to establish novel agricultural production practices that not only result in fewer adverse impacts on health and the environment but also improve the resilience and growth of the plants. In this work, an analysis of the impact of plant growth-promoting bacteria (PGPB) and chitosan on plant growth and protection has been conducted, emphasizing the crucial bioactivities of the resistance of the plants to both biotic and abiotic stressors. These include inducing phytohormone production, mobilization of insoluble soil nutrients, biological nitrogen fixation, ethylene level regulation, controlling soil phytopathogens, etc. Moreover, some relevant aspects of chitin and chitosan are discussed, including their chemical structures, sources, and how their physical properties are related to beneficial effects on agricultural applications and mechanisms of action. The effects of PGPB and chitosan on photosynthesis, germination, root development, and protection against plant diseases have been compared, emphasizing the intriguing similarities and synergistic effects observed in some of these aspects. Although currently there are limited studies focused on the combined application of PGPB and chitosan, it would be important to consider the similarities highlighted in this work, and those that may emerge in future studies or through well-designed investigations, because these could permit advancing towards a greater knowledge of these systems and to obtain better formulations by combining these bioproducts, especially for use in the new contexts of sustainable agriculture. Thus, it seems feasible to augur a promising near future for these combinations, considering the wide range of possibilities offered by chitinous biomaterials for the development of innovative formulations, as well as allowing different application methods. Likewise, the studies related to the PGPB effects on plant growth appear to be expanding due to ongoing research to test on plants the impacts of microorganisms derived from different environments, whether known or recently discovered, making it a very exciting field of research.